Soil fertility status as affected with and without farmyard manure in kharif crops and fertilizer levels in barley (Hordeum vulgare) - SHAKTAWAT, R P S; SHEKHAWAT, P S (The Indian Journal of Agricultural Sciences, 2010)
A field investigation was carried out during rainy (kharif) and winter (rabi) seasons of 2003–04 and 2004–05 on sandy loam soils to study the effect of fertilizer levels and preceding crops grown with and without farmyard manure on soil fertility status after barley. Clusterbean (Cyamposis tetragonoloba L. Toubert) – barley (Hordeum vulgare L.) crop sequence significantly increased the nitrogen status of soil (139 kg/ha). Whereas, available phosphorus status was significantly higher (19.45 kg/ha) under pearl millet [Pennisetum glaucum L.R. Br. emend. Stuntz.] – barley crop sequence. Application of farmyard manure significantly increased the available nitrogen, phosphorus and potassium content in soil compared with the control. Barley crop fertilized up with the 120 kg N + 60 kg P2O5/ha significantly increased the available phosphorus status of soil.